PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PERTUMBUHAN AKTIVA, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAAN–PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013- 2017) - Nuril Huda, 14.05.51.0183; Kartika, Andi (Students' Journal of Economic and Management, 2018)
This study aims to examine the influence of Profitability, Liquidity, Asset Structure, Company Size, Asset Growth, and Sales Growth on Capital Structure of LQ-45 companies listed on Indonesia Stock Exchange (IDX) for the period of 2013-2017. This study was conducted using secondary data. The population in this study are all companies incorporated in the LQ-45 index year 2013-2014. The sample in this research use purposive sampling method. The method of analysis used in this research is multiple linier regression analysis method. The result showed that ROA had positive and not significant effect on DER, CR had negative and significant effect on DER, SA had negative and significant effect on DER, SIZE had negative and not significant effect on DER, AG had positive and significant effect on DER, SG negative effect and significant against DER. The Adjusted R Square value is 0.260 this means the dependent variable can be explained by the independent variable, while the remaining 74.0% is explained by other causes outside the model. Keyword: Profitability (ROA), Liquidity (CR), Asset Structure (SA), Company Size (SIZE), Asset Growth (AG), Sales Growth (SG) and Capital Structure (DER)